Examining an Online Microbiology Game as an Effective Tool for Teaching the Scientific Process(†) - Bowling, Kristi G. (American Society of Microbiology, 2013)
This study investigates the effectiveness of the online Flash game Disease Defenders in producing knowledge gains for concepts related to the scientific process. Disease Defenders was specifically designed to model how the scientific process is central to a variety of disciplines and science careers. An additional question relates to the game’s ability to shift attitudes toward science. Middle school classes from grades six to eight were assigned to the experimental group (n = 489) or control group (n = 367) and asked to participate in a three-session intervention. The sessions involved completing a pretest, a game play session, and taking a posttest. Students in the experimental group played Disease Defenders while students in the control group played an alternative science game. Results showed a significant increase in mean science knowledge scores for all grades in the experimental group, with sixth grade and seventh grade students gaining more knowledge than eighth grade students. Additionally, results showed a significant positive change in science attitudes only among sixth graders, who also rated their satisfaction with the game more favorably than students in higher grades. No differences in mean test scores were found between genders for science knowledge or science attitudes, suggesting that the game is equally effective for males and females.